1999
DOI: 10.3143/geriatrics.36.861
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and Background Factors in Community-Dwelling Older Persons.

Abstract: Table 1 Distribution of survey subjects by happiness, by age and sex CI indicates cofidence interval. and Background Factors in Community-Dwelling Older Persons Ryuichi Kawamoto1), Takaaki Doi1), Akihiro Yamada1), Masanobu Okayama2), Kouki Tsuruoka2), Motomi Satho3) and Eiji Kajii2) In order to maintain and improve mental health of elderly people living in the community, a cross sectional survey was conducted to elucidate their happiness and background factors. The subjects were elderly persons living in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…While educational attainment was associated with SRH in the young age group, adjusted household income was associated with self-rated physical health in the middle-age and old-age groups [33]. Some previous studies using SRH for elderly individuals in Japan have identified that factors such as years of education, income, depression, stress, sense of coherence, hobby activities, joining in social activities, and getting social support are strongly related to HRQOL [23,24,[34][35][36][37]. More studies are expected to investigate relationships between each factor and Japanese HRQOL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While educational attainment was associated with SRH in the young age group, adjusted household income was associated with self-rated physical health in the middle-age and old-age groups [33]. Some previous studies using SRH for elderly individuals in Japan have identified that factors such as years of education, income, depression, stress, sense of coherence, hobby activities, joining in social activities, and getting social support are strongly related to HRQOL [23,24,[34][35][36][37]. More studies are expected to investigate relationships between each factor and Japanese HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have pointed out that Japanese HRQOL might be affected by factors such as age, sex, socioeconomic status, health-related behaviors, some diseases, and social networks [33][34][35][36][37][38][39][40][41]. A previous study using SRH in Japan revealed that female educational attainment shows significant linear associations with SRH [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ample evidence demonstrates that people are happier with better social support or more social involvement (Baumeister & Leary, 1995;Booth, 1992;Brim, 1974;Chan & Lee, 2006;Gundelach & Kreinar, 2004;Jopp & Rott, 2006;Kehle & Bray, 2003;Lane, 1994Lane, , 2000Lu, 1999;Lu, Shih, Lin, & Ju, 1997;Natvig, Albrektsen, & Qvarnstrom, 2003;Neto, 2001;North, Holahan, Moos, & Cronkite, 2008;Perneger, Hudelson, & Bovier, 2004;Ryuichi et al, 1999;Singh et al, 2004;Uchida, Norasakkunkit, & Kitayama, 2004). Happiness is positively associated with self-esteem (Baumeister, Campbell, Krueger, & Vohs, 2003), and self-esteem reflects belongingness (Leary & Baumeister, 2000).…”
Section: Social Supportmentioning
confidence: 99%
“…Turner (7) ercise gained a lower average score in happiness than those with high levels of physical activity. Happiness had a direct relationship with improvement of the quality of appetite, sleep, memory, family relationships, friendship, family status and the elderly people's mental health and quality of life (8).…”
Section: Introductionmentioning
confidence: 99%